The effect of manipulating the pre-exercise template on time-trial performance - Jaime, S.; Nyberg, K.; Condello, G.; Casolino, E.; Dodge, C.; Marroyo-Rodriguez, J.; Mikat, R.; Porcari, J. P.; Wright, G.; Foster, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Responsive control of power output (PO) is essential in order to achieve optimal performance with acceptable homeostatic disturbances. It is known that an athlete will decrease their PO following a decrease in arterial oxygen saturation (SaO2), and that during this decrease in PO, the athlete regulates the sense of perceived exertion (RPE)(Johnson et al., 2009; Joseph et al., 2008). The purpose of this study was to understand whether homeostatic disturbances prior to a time trial influence competitive exercise intensity would reset the pre-exercise template, reflected by the PO during the first 1 km of a 5 km time trial. Methods: Seven well-trained subjects performed a VO2 max test, two habituation trials, and four randomly ordered, single blinded 5 km cycle ergometer time trials with warm-up (WU) and time trial (TT) conditions. Including NN (normoxic WU/hypoxic TT), NH (normoxic WU/hypoxic TT), HH (hypoxic WU/hypoxic TT), or HN (hypoxic WU/normoxic TT) (hypoxic FIO2 = 0.15, normoxic FIO2 = 0.21). Results: The hypoxic WU (HR: 163bpm, RPE: 5.9, HLa: 7.6 mmol/L, SaO2: 84%) was much more challenging than the normoxic WU (HR: 162bpm, RPE: 4.2, HLa: 5.2mmol/L, SaO2: 97%). Despite this, there was no significant difference (p>0.05) between the warm-up conditions in PO during the first 500m of the time trial (NN: 272W ±76W, NH: 283W ±67W, HH: 270W ±54W, HN: 284W ±79W). During the second 500m, PO was decreased in the hypoxic racing conditions (264W ±46W vs 244W ±49W), without reference to hypoxia/normoxia during WU. The SaO2 was significantly different (p<0.00) during normoxic (96% ±0.59%) compared to hypoxic (83% ±0.61%) at all time points. Discussion: The central governor concept suggests that PO might be reduced following a more challenging WU (attributable to hypoxia) on the premise that the exerciser might expect a greater challenge to homeostasis. However, the results demonstrate that despite much more challenging conditions during the hypoxic WU, the PO during the opening part of the time trial was not affected, demonstrating the robustness of the pre-exercise template.